Transcriptome reveals the landscape of alveolar macrophages exposed to combined hypoxia with cigarette smoke extract - Liu, Qing; Zhang, Yushi; Duan, Ruirui; Li, Wanheng; Hou, Xuan; Chen, Yiling; Li, Baicun; Yang, Ting (Respiratory research, 2025)
Background Chronic obstructive pulmonary disease (COPD) is a complex and heterogeneous chronic inflammatory disease that is one of the leading causes of age-standardised deaths globally. While studies have investigated altitude's effects on COPD, none have explored alveolar macrophage homeostatic alterations during its pathogenesis at high altitudes. Methods We constructed a high-altitude COPD model through exposure of mouse alveolar macrophages (MH-S) to hypoxia and cigarette smoke extract (CSE). Hypoxia-inducible factor (HIF) expression was quantified in MH-S cells exposed to hypoxia combined with CSE and in the control group. HIF-1α short hairpin RNA (shRNA) was added to the MH-S cells. Transcriptome was used to characterise downstream signalling pathways of HIF-1α in MH-S cells treated with hypoxia and CSE exposure. Standard molecular techniques were used to validate the RNA sequencing results. Results HIF-1α but not HIF-2α was significantly up-regulated in MH-S cells after exposure to hypoxia and CSE. RNA-sequencing analysis of MH-S cells showed the relevant pathways downstream of HIF-1α are mainly inflammation, glycolysis, M1 polarization, extracellular matrix remodelling and angiogenesis. Validation of RNA-sequencing analysis confirmed that the above signalling pathways were abnormally up-regulated after CSE exposure, and that combined hypoxic exposure further exacerbated the induced aberrant up-regulation, which was inhibited after treatment with HIF-1α shRNA. Conclusion Downstream HIF-1α signalling pathways drive inflammation, M1 macrophage polarization, glycolysis, extracellular matrix remodelling, and angiogenesis, potentially disrupting alveolar macrophages homeostasis during high-altitude COPD pathogenesis. This disruption may be one reason underlying the high prevalence of COPD in high-altitude regions.